Analisis Kualitas Teh Celup Herbal Sebagai Minuman Fungsional - Ita Fatkhur Romadhoni; Any Sutiadiningsih; Niken Purwidiani; Lilis Sulandari; Ila Huda (Politeknik Kampar, 2023)
The potential for diversification of herbal drinks is increasing along with a healthy lifestyle. This research aims to develop herbal drinks in the form of tea bags that are practical and economical in terms of proportions and selling price. There were seven herbal tea samples tested with the proportion of spices, namely mangosteen peel, ginger, lemongrass, cherry leaves, lime leaves (P1= 1:1:1:1:1:1), (P2= 1:2:1 :1:1:1:1), (P3= 1:1:2:1:1:1:1), (P4= 1:1:2:1:1:1), (P5= 1:2 :2:1:1:1:1:1:1:1:1:1:1:1:1:1:1:1:1:1:2:1:1:1:1:1:1 ): 1:1:2:1:1:1:1), (P5 1:1:1:1:1:2:1:1), (P6 = 1:1:1:1:1:2 :1), and (P7 = 1:1:1:1:1:1:2) The hedonic test method is used to get the best results based on the quality of herbal tea with color, aroma and taste parameters. The sample of respondents consisted of 100 MSME assistants. The research results showed that the best results were with the composition P3 = 1:1:2:1:1:1 in terms of aroma and taste of herbal tea bags. Meanwhile, in terms of the level of importance of herbal teabags, the panel considered the color aspect to be the most important factor, suggesting the taste and aroma of herbal teabags. Meanwhile, the selling price was obtained at IDR 12,500/pack. The results of this research indicate that herbal tea bags can be accepted by the market so that further research is needed regarding chemical content tests.